The gastrointestinal helminths of Rattus niobe (Rodentia: Muridae) with descriptions of two new genera and three new species (Nematoda) from Papua New Guinea and Papua Indonesia - Smales, L. R. (Zootaxa, 2016)
Cestodes, to be identified elsewhere, the acanthocephalan Moniliformis moniliformis and 15 species of nematode including 2 new genera, a new species and 2 putative new species from the families Heligmonellidae and Oxyuridae, as well as juveniles and a putative heligmonellid that could not be fully identified, were collected from the digestive tracts of 34 Rattus niobe (Muridae: Murinae: Rattini) from Papua, Indonesia and Papua New Guinea. The ascaridid, Toxocara mackerrasae, the chabertiid Cyclodontostomum purvisi, the heterakid Heterakis sp., the spirurids Protospirura kaindiensis and P. muricola the subulurid Subulura andersoni and the trichurids Eucoleus sp. and Trichuris muris have been reported previously from endemic Rattus spp. Syphacia (Syphacia) niobe n. sp. was distinguished from its congeners by a combination of characters including a round cephalic plate, the lack of cervical and lateral alae, a longer male tail and an attenuated female tail. Nugininema titokis n. gen., n. sp. differs from all other genera in the Heligmonellidae in the characters of the synlophe, 10–17 ridges orientated subfrontally at mid body and 2 right ventral ridges hypertrophied anteriorly. Rodentanema aenigma n. gen., n. sp. differs from all other genera in the Heligmonellidae in the characters of the synlophe 6–7 ridges at mid body not symmetrical in relation to frontal axis. Species richness of the nematode assemblage was similar to that reported for Rattus leucopus in Papua New Guinea, with about 90% of possible species found as indicated by bootstrap analysis. Species composition included 6 species unique to R. niobe and 7 species reported from at least one other species of Rattus indigenous to New Guinea, as well as juvenile worms, probably ascaridids.